Solar-type periodicities in the climate variability of Northern Fennoscandia during the last three centuries: Real influence of solar activity or natural instability in the climate system - Ogurtsov, Maxim; Helama, Samuli; Jalkanen, Risto; Jungner, Högne; Lindholm, Markus; Veretenenko, Svetlana
2021